• ## Discover

1. Home >
2. All Categories >
3. Science & Mathematics >
4. Mathematics >
5. Resolved Question
Member since:
January 02, 2011
Total points:
163 (Level 1)

## Resolved Question

Show me another »

# Algebra 2 help! thanks just 3 questions?

What is the 20th term of the arithmetic sequence 4, –2, –8, … ?

–110

–116

–122

–128

What is the sum of a 17–term arithmetic sequence where the first term is 9 and the last term is –87?

–718

–739

–663

–644

What is the 17th term of the arithmetic sequence 17, 21, 25, … ?

73

77

81

85
Member since:
May 09, 2009
Total points:
71,848 (Level 7)

## Best Answer - Chosen by Voters

1).
What is the 20th term of the arithmetic sequence 4, –2, –8, … ?
–110

2).
What is the sum of a 17–term arithmetic sequence
where the first term is 9 and the last term is –87?
Difference = 96/17
5< D < 6
9 + 4 + (-1) + (-6) + ...... +(-71)-----> -527
9 + 3 + (-3) + (-9) + ...... +(-87)------) -663

–663

3).
The 17th term of the arithmetic sequence 17, 21, 25, … ?
81

There are currently no comments for this question.

• by John G
Member since:
September 15, 2006
Total points:
504 (Level 2)
1. Looks like it follows the equation 10-6n where n is the number of the term
thus the 20th term is 10-6(20) or 10-120 = -110

2. Let the equation be A+nB
the first term is A+B = 9
the 17th term is A+17B=-87

equation 2 less equation 1 is 16B = -96..........B = -6 .......A = 15

so the 17-term sequence starts with 15-6(1)...15-6(2)......to 15-6(17)

the sum is 15(17)-6(sum 1 to 17)........................sum (1-17) is 17(17+1)/2 = 153

thus 15(17) -6(153)
= 255 - 918
= -663

3. looks like the formula there is 13 + 4n
so the 17th term is 13 + 4(17)
= 13 + 68
= 81
• by Kiki
Member since:
April 19, 2011
Total points:
150 (Level 1)
You are using the equation An= A1 + (n-1)d
1) A1= 4(first number) n= 20( number of term you want) d= -6 ( you are taking away 6 to get to each new term)
Now just plug in and solve:
An= 4 + (20-1)(-6)

Now use the equation Sn= n/2(An+A1)
2) n=17 An=-87 A1=9
Plug in and solve:
Sn= (17/2)(-87 + 9)

Use An= A1 + (n-1)d again
3) n=17 A1=17 d=+4
Plug in and solve:
An= 17 + (17-1)(4)

### Source(s):

Math Teacher
• Member since:
February 14, 2010
Total points:
865 (Level 2)
1) -110
2)-718
3) 79

### Source(s):

pre-algebra student [;
• Member since:
November 29, 2007
Total points:
639 (Level 2)
the last one is 85